Equity research –advanced micro devices (AMD) - Teles, Filipa Simão (2020)
Advanced Micro Devices (AMD) is a Silicon Valley-born semiconductor company,that had its IPO in 1972. Despiteits rough past, in the most recent years,AMD has beenable togaincompetitive advantage in relation to its industry peers,as well asmarket sharedue to its continuous innovative products’ lines of EPYC and Ryzen processors, and Radeon graphics.Furthermore, recentlyestablished partnerships and launched products give the company good growth prospects, in the near future.For these reasons an Equity Research Report was conducted on AMD, in order to get to a fair value of the stock.AMD’s valuationin the reportwas assessed through the Discounted Cash Flow (DCF)method, considering various factors that could affect the company’s financial statement lineitems.Among those factors are the Average Selling Price of its products, Units Shipments, Gross Margin, investments in innovation (R&D), and several partnerships alongside with the company’s Market Share.A scenario analysison the effects of the tariffs, comingfrom the Trade War,was also conductedon AMD’s price.The price target arrived for December 31, 2020 was $52.75, leading to a BUYinvestment recommendation, considering normal market conditions.